1997
DOI: 10.1097/00005373-199710000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Direct Induction of Acute Lung and Myocardial Dysfunction by Liver Ischemia and Reperfusion

Abstract: Ischemic and reperfused liver can directly induce myocardial and pulmonary dysfunction, presumably by oxidant-induced injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 29 publications
2
51
0
1
Order By: Relevance
“…Oxygen stress may induce MOF, which is clinically significant. Data from this and previous studies [23,24,[29][30][31][32][33][34][35][36] suggest that a number of clinical features of renal dysfunction in the presence or following PNP may in fact be due to low flow/reflow situations, and thus may relate to XO-derived radical oxygen species (ROS) activity, as demonstrated herein for the C8 mmHg groups. We have previously described the toxic effects of high XO activity in the lungs [23].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Oxygen stress may induce MOF, which is clinically significant. Data from this and previous studies [23,24,[29][30][31][32][33][34][35][36] suggest that a number of clinical features of renal dysfunction in the presence or following PNP may in fact be due to low flow/reflow situations, and thus may relate to XO-derived radical oxygen species (ROS) activity, as demonstrated herein for the C8 mmHg groups. We have previously described the toxic effects of high XO activity in the lungs [23].…”
Section: Discussionsupporting
confidence: 56%
“…We then argued that, when tissues are exposed to metabolic stress such as improper circulation or lack of oxygen-potentially occurring during PNP-tissue xanthine dehydrogenase (XDH) is converted to XO. Upon reperfusion or reoxygenation, the latter, in the presence of adequate substrates and abundant molecular oxygen influx into the post-hypoxic/ischemic tissue [36], generates oxidants such as the superoxide anion (O 2 -), hydrogen peroxide (H 2 O 2 ), and the hydroxyl radical (.OH) [34,37]. These cascades of events may start after the advent of tissue damage-here due to impediment to the vascular tree-even if followed by volume or pressure resuscitation, as demonstrated herein.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic ischemia has been documented to cause inflammatory lung injury. 5 In other studies, acute myocardial injury 6 and renal injury was attributed to hepatic ischemia.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have shown that the hepatic IR injury is associated with injury to remote organs, such as the lungs (14,15) and kidneys (16,17). This may complicate the delineation of the effects of hepatic IR on the canalicular efflux transporters after in vivo administration of RH-123.…”
Section: Introductionmentioning
confidence: 99%